Ensilability of Biomass From Effloresced Flower Strips as Co-substrate in Bioenergy Production - Müller, Jürgen; Hahn, Juliane (Frontiers in Bioengineering and Biotechnology, 2020)
Flower strips are grown to an increasing degree in order to enhance the ecological value of agricultural landscapes. Depending on their profitable life span and the crop sequence, the strips’ biomass must be mulched after flowering to enable repeated tillage. A promising alternative is the use of the flower strips’ biomass as a co-substrate for biomethanisation - thereby contributing to the climate-friendly generation of energy. This potential bioenergy substrate occurs only seasonally and is commonly produced only in limited quantities at a farm scale. To realize the additional benefit of flower strips as energy supplier, stock piling of the strips’ biomass is required. However, information about the ensilability of flower strip biomass is still rare. We conducted a two-year study to analyze the ensilability of pure biomass from effloresced flower strips and mixtures of flower strip biomass with 33 % and 67 % whole crop maize, respectively. Ensiling took place in 2 l model silos at laboratory scale after chopping the substrate. Before ensiling several chemical characteristics of the biomass stock were determined to assess the substrate’s biochemical ensilability potential (DM, WSCH, buffering capacity, nitrate content). The process-engineered ensiling success after 90 days was determined based on fermentation patterns. The ensilability potential of the pure flower strip substrates reached modest levels (fermentability coefficients according to Weißbach vary around the threshold of 45). Nevertheless, acceptable silage qualities were achieved under the laboratory conditions (pH ranging from 4.2 to 4.7). Compared to pure flower strip biomass the addition of maize noticeably improved both the substrate’s biochemical ensilability potential and the quality of realized process-engineered silage. We conclude that a mixture of 33% biomass from flower strips with 67% whole crop maize can be regarded as a recommendable ratio, if proper ensiling technology is applied.